2021
DOI: 10.3390/cancers14010092
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Testing in Older Patients Treated for an Advanced or Metastatic Non-Squamous Non-Small-Cell Lung Cancer: The French ESME Real-Life Multicenter Cohort Experience

Abstract: Background: Genomic and immunologic tumor biomarker testing has dramatically changed the prognosis of patients, particularly those treated for advanced/metastatic non-squamous non-small-cell lung cancer (aNSCLC) when access to targeted agents is available. It remains unclear whether older patients have access to therapy-predictive biomarker testing techniques in the same proportion as younger patients. This study aims to compare the proportion of biomarker testing performed in non-squamous aNSCLC at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Real-world data of predictive biomarker testing rates in patients with NSCLC is limited, and the available information is often outdated or grouped with older data ( Table 3 ). 7 , 44 , 70 , 72 , 76 However, recent studies from England, Spain, the Netherlands, and Norway have demonstrated high testing rates for EGFR and ALK . 71 , 74 , 75 , 77 It should be noted that testing rates of predictive biomarkers introduced after EGFR and ALK tend to be lower, but should be interpreted with caution, due to the often limited reporting of these biomarkers and potential variations in testing methodologies over time.…”
Section: Predictive Biomarker Testing Ratesmentioning
confidence: 99%
“…Real-world data of predictive biomarker testing rates in patients with NSCLC is limited, and the available information is often outdated or grouped with older data ( Table 3 ). 7 , 44 , 70 , 72 , 76 However, recent studies from England, Spain, the Netherlands, and Norway have demonstrated high testing rates for EGFR and ALK . 71 , 74 , 75 , 77 It should be noted that testing rates of predictive biomarkers introduced after EGFR and ALK tend to be lower, but should be interpreted with caution, due to the often limited reporting of these biomarkers and potential variations in testing methodologies over time.…”
Section: Predictive Biomarker Testing Ratesmentioning
confidence: 99%
“…The most common reason for the lack of recruitment of older patients with cancer is selective eligibility criteria, excluding older patients with functional decline, comorbid conditions and/or prior malignancy [ 1 ]. While specific guidelines on treating cancer in older patients from scientific societies and systematic review of the literature can help physician in daily practice [ 2 , 3 , 4 ], these guidelines are not always followed [ 4 ].…”
mentioning
confidence: 99%